The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3171/2015.4.jns15484
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of tenascin-C and attenuation of blood-brain barrier disruption following experimental subarachnoid hemorrhage in mice

Abstract: A neurysmAl subarachnoid hemorrhage (SAH) is one of the most life-threatening cerebrovascular disorders, with high mortality and morbidity rates. 26,33 Delayed cerebral ischemia (DCI) remains the most important cause of morbidity and mortality in those patients who survive the initial bleeding. 20 Recent studies have reported that early brain injury (EBI), as well as cerebral vasospasm, is a major cause of DCI following SAH. 20EBI occurs before the onset of cerebral vasospasm and may cause DCI with no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 37 publications
(77 reference statements)
0
61
0
2
Order By: Relevance
“…This suggests that the reduction in the GFAP + area at later stages (28 dpi) is not due to an initially reduced upregulation of this protein. We further noted much higher levels (more than 100×) of tenascin‐C (Tn‐C) in WT compared to CCR2 −/− , an intriguing observation given the adverse effects Tn‐C has on the lesion size and scar formation . Reduced Tn‐C levels surrounding the injury site in CCR2 −/− mice at 5 dpi was confirmed by immunostaining (Fig EV5).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…This suggests that the reduction in the GFAP + area at later stages (28 dpi) is not due to an initially reduced upregulation of this protein. We further noted much higher levels (more than 100×) of tenascin‐C (Tn‐C) in WT compared to CCR2 −/− , an intriguing observation given the adverse effects Tn‐C has on the lesion size and scar formation . Reduced Tn‐C levels surrounding the injury site in CCR2 −/− mice at 5 dpi was confirmed by immunostaining (Fig EV5).…”
Section: Resultsmentioning
confidence: 63%
“…noted much higher levels (more than 100×) of tenascin-C (Tn-C) in WT compared to CCR2 À/À , an intriguing observation given the adverse effects Tn-C has on the lesion size and scar formation [41].…”
Section: Reduced Infiltration Of Ccr2 + Monocytes Increases Astrocytementioning
confidence: 99%
“…In experimental SAH, POSTN caused EBI or BBB disruption via the activation of mitogen-activated protein kinases (MAPKs) and matrix metalloproteinase (MMP)-9, interacting with another matricellular protein tenascin-C [13]. MAPKs and MMP-9 are well known to cause the degradation of cerebral microvessel basal lamina and tight junction protein zona occludens-1, resulting in BBB disruption and brain edema formation after SAH [31,32]. A more recent study also showed the possible involvement of POSTN in the development of EBI or BBB disruption after experimental SAH [28].…”
Section: Discussionmentioning
confidence: 99%
“…30,32 TNC also caused brain injuries after experimental SAH. 12,29 Cilostazol-a selective inhibitor of phosphodiesterase Type III and a cyclic adenosine monophosphate (cAMP)elevating agent-is a clinically available antiplatelet agent and has pleiotropic actions, including vasodilatory and antiinflammatory effects. 25 It has been suggested that cilostazol reduces symptomatic vasospasm and is relatively widely administered to SAH patients in Japan.…”
mentioning
confidence: 99%